Insight Into Formation Processes of Layered Ejecta Craters on Mars From Thermophysical Observations. Issue 12 (2nd December 2021) - Hoover, R. H.; Robbins, S. J.; Putzig, N. E.; Riggs, J. D.; Hynek, B. M.
Abstract: Understanding the morphological characteristics of craters that are indicative of their formation environment can provide insight into surface geology. Layered ejecta (LE) craters, found on Mars and some other planetary bodies, have been hypothesized to have formed as a result of either interaction with subsurface volatiles (volatile fluidization model) and/or with the atmosphere (atmospheric entrainment model). Formation of LE craters by either model should result in different grain size distributions throughout the ejecta deposit. Using thermal inertia to infer surface properties, we investigated LE craters and their ejecta deposits in an effort to distinguish between possible LE formation processes on Mars. We used thermophysical properties of crater ejecta to determine grain size distribution, to model horizontal mixtures and vertical layering, and to identify materials present within the ejecta. We assessed the thermal properties of 50 uniformly sampled LE craters using Mars Odyssey Thermal Emission Imaging System (THEMIS) and Mars Global Surveyor Thermal Emission Spectrometer (TES) data. Our THEMIS analysis identifies 12 craters with grain size distributions consistent with the volatile fluidization model, 3 craters that have characteristics potentially associated with either model, and 22 craters that do not exhibit characteristics matching either model. Our TES analysis identifies 11 craters with characteristics consistent with the volatile fluidization model and 8 craters that are consistent with the atmospheric entrainment model. While some observations of grain size distributions provide evidence for either or both models, there is not overwhelming support for either model, potentially due to uncertainties of derived thermal inertia data. Plain Language Summary: Impact craters are found throughout the solar system and can tell us about the geology around them. A specific type of crater, layered ejecta (LE) craters, may help us identify underground ice on Mars and other planetary bodies. LE craters are hypothesized to form when the energy of an impactor causes sub‐surface ice to become fluid or gas and flow outward. This hypothesis requires the presence of sub‐surface ice, and if it was found to be true, then identifying LE craters could be used to identify the locations of subsurface ice and water in the solar system. LE craters are identified by their ejecta deposits, which is the material that resettles around a crater following an impact. Grain size distributions throughout the ejecta deposits can tell us about their formation. We examined the grain size distribution of ejecta deposits surrounding 50 LE craters on Mars and looked at their thermal inertia, which is how well material holds onto heat, where smaller sand particles release their heat more quickly than large particles like boulders. Overall, the observed grain size distributions and thermal properties do not provide overwhelming support for the hypothesis that requires sub‐surface ice and thus further research is warranted. Key Points: The formation process of Martian layered ejecta (LE) craters could have important implications for the presence of subsurface volatiles In a sampling of 50 LE craters, we find no distinct relationship between crater type and trends in apparent thermal inertia Results provide no overwhelming support for either the atmospheric entrainment or the volatile fluidization model for LE crater formation